IMMEDIATE EFFECT OF ICE WATER IMMERSION AS PRE - COOLING ON ENERGY EXPENDITURE AND STEP COUNT AMONG AMATEUR YOUNG - ADULT MINIMARATHON RUNNERS - Maghfiroh, Rinna Ainul; Wanpen, Sawitri; Buranruk, Orawan; Pimdee, Atipong; Chanavirut, Raoyrin; Srikamsuk, Udomvit; Punnasiri, Tanarak; Nathonglor, Kamonrat; Sangpara, Paramaporn; Konharn, Kurusart (Academic Journal of Thailand National Sports University, 2023)
This study aimed to investigate the immediate effect of ice water immersion (CWI) on energy expenditure (EE) and step count among amateur young - adult mini marathon runners. They were recruited and divided into 2 groups equally (n = 15), the non - CWI group and the CWI group (n = 15). Non - CWI as the control group performed dynamic stretching and the CWI group were applied by 8 - 10°C cold water immersion for 5 minutes equally. EE and step count were carried out by ActiGraph accelerometer during 16 - minute running on a treadmill. Data analysis was performed by using Paired sample t - test and an independent sample t - test. Results showed a significant decrease in EE of the control group (49.34 vs. 44.23 kcal, p < 0.001) but there was no significant difference in step count (p = 0.57). While it did not find any significant difference in EE among the CWI group (p > 0.05) but in this group, there was a considerable increase in step count (2041.79 vs. 2165.64, p = 0.02). The findings of this study conclude that CWI increased step count which would be associated with the reduction of running speed. But it did not affect any changes in EE.